Southeast Asian Countries' Diplomacy Amidst Covid-19 from Islamic Perspectives - Sally, Novian Uticha (UIN Sunan Ampel Surabaya, 2022)
The emergence of Covid-19 at the end of 2019 became the starting point for a new multidimensional threat to the world. This pandemic situation is an obstacle to the relationship maintenance among nations which are generally carried out traditionally. Various innovations are needed because there is a shifting paradigm in various sectors of life rapidly. Some countries have made several adjustments related to its diplomacy with other countries to ensure the continuity of relations between countries and the welfare of their citizens in this pandemic era. In the Islamic world, the control of pandemic has been done before so that it can be one of the solution options. This study begins by describing the changes in diplomacy carried out by Southeast Asian countries with Muslim majority populations during the pandemic. The next step was done by analyzing the changes in diplomacy that have been carried out by those countries with Islamic diplomacy. This study aims to determine the extent to which the diplomatic changes carried out by these countries are viewed from the Islamic perspectives. The results obtained show that several diplomatic activities carried out by those Southeast Asian countries are in accordance with Islamic diplomacy. However, there are still some aspects of Islamic diplomacy that these countries can adapt in the future.